2018
DOI: 10.15578/jpbkp.v13i2.536
|View full text |Cite
|
Sign up to set email alerts
|

Sitotoksisitas dan Induksi Apoptosis Ekstrak Etanol Teripang holothuria atra Jaeger, 1833 pada beberapa Sel Kanker

Abstract: ABSTRAKTeripang Holothuria atra merupakan biota laut yang banyak ditemukan di perairan Indonesia yang termasuk dalam filum Echinodermata dan berpotensi sebagai antikanker. Penelitian ini bertujuan untuk mengetahui sitotoksisitas dan induksi apoptosis ekstrak etanol teripang H. atra secara in vitro terhadap beberapa sel lestari. Pengujian sitotoksisitas dilakukan dengan metode MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide) menggunakan sel HeLa, T47D, WiDr dan sel normal Vero, sedangkan uji … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The anticancer activity of this immunomodulator is caused by anti-inflammatory, antioxidant, and induction effects of apoptosis, anti-angiogenesis, and anti-metastasis (Mohamed et al 2017). Previous studies (Putram et al 2017;Halimatushadyah et al 2018) also revealed that H. atra extract exhibited cytotoxicity to T47D, HeLa, MCF7, and WiDr cells. The anticancer mechanism of saponin compounds found in H. atra in T47D cells occurs through the induction of apoptosis and cell cycle arrest (Nursid et al 2019).…”
Section: Discussionmentioning
confidence: 95%
“…The anticancer activity of this immunomodulator is caused by anti-inflammatory, antioxidant, and induction effects of apoptosis, anti-angiogenesis, and anti-metastasis (Mohamed et al 2017). Previous studies (Putram et al 2017;Halimatushadyah et al 2018) also revealed that H. atra extract exhibited cytotoxicity to T47D, HeLa, MCF7, and WiDr cells. The anticancer mechanism of saponin compounds found in H. atra in T47D cells occurs through the induction of apoptosis and cell cycle arrest (Nursid et al 2019).…”
Section: Discussionmentioning
confidence: 95%
“…Sea cucumber extract H. atra has the ability to inhibit cancer cell growth, especially in T47D cancer cells. The inhibitory ability is mediated through the mechanism of apoptosis, which has been proven through flow cytometry testing and double staining analysis (Halimatushadyah et al, 2018). The results showed that some natural and semisynthetic triterpenoids have tumor inhibitory properties and even cytotoxicity against breast cancer cells, including T47D (Okuda, 2016).…”
Section: Introductionmentioning
confidence: 95%
“…Cytotoxicity test carried out according to the method, 5,21,22 with slight modification. Suspension of HT-29 and AdenoCa pT3N1cM1 cells, which were with a density of 1 x 10 6 cells/100 μl, were inserted media into 96-well disc and incubated for 12 h in a CO 2 incubator (N-Biotek).…”
Section: Cell Preparationmentioning
confidence: 99%